Electron delocalisation in conjugated sulfur heterocycles probed by resonant Auger spectroscopy. Issue 14 (28th March 2022) - Martins, Jessica B.; de Moura, Carlos E. V.; Goldsztejn, Gildas; Travnikova, Oksana; Guillemin, Renaud; Ismail, Iyas; Journel, Loïc; Koulentianos, Dimitrios; Barbatti, Mario; Lago, Alexsandre F.; Céolin, Denis; Rocco, Maria Luiza M.; et al.
Abstract : Conjugation and hyperconjugation in core-excited states of organosulfur molecules probed by a novel experimental and theoretical approach using resonant Auger spectroscopy. Abstract : We propose a novel approach for an indirect probing of conjugation and hyperconjugation in core-excited molecules using resonant Auger spectroscopy. Our work demonstrates that the changes in the electronic structure of thiophene (C4 H4 S) and thiazole (C3 H3 NS), occurring in the process of resonant sulfur K-shell excitation and Auger decay, affect the stabilisation energy resulting from π-conjugation and hyperconjugation. The variations in the stabilisation energy manifest themselves in the resonant S KL2, 3 L2, 3 Auger spectra of thiophene and thiazole. The comparison of the results obtained for the conjugated molecules and for thiolane (C4 H8 S), the saturated analogue of thiophene, has been performed. The experimental observations are interpreted using high-level quantum-mechanical calculations and the natural bond orbital analysis.